Enhanced Photoelectrochemical Properties of Cu2O-loaded Short TiO2 Nanotube Array Electrode Prepared by Sonoelectrochemical Deposition - Liu, Yanbiao; Zhou, Haibin; Li, Jinhua; Chen, Hongchong; Li, Di; Zhou, Baoxue; Cai, Weimin (Nano-Micro Letters, 2011)
Copper and titanium remain relatively plentiful in earth crust. Therefore, using them in solar energy conversion technologies are of significant interest. In this work, cuprous oxide (Cu2O-modified short TiO2 nanotube array electrode was prepared based on the following two design ideas: first, the short titania nanotubes obtained from sonoelectrochemical anodization possess excellent charge separation and transportation properties as well as desirable mechanical stability; second, the sonoelectrochemical deposition technique favours the improvement in the combination between Cu2O and TiO2 nanotubes, and favours the dispersion of Cu2O particles. UV-Vis absorption and photo- electronchemical measurements proved that the Cu2O coating extended the visible spectrum absorption and the solar spectrum-induced photocurrent response. Under AM1.5 irradiation, the photocurrent density of the composite electrode (i.e. sonoelectrochemical deposition for 5 min) was more than 4.75 times as high as the pure nanotube electrode. Comparing the photoactivity of the Cu2O/TiO2 electrode obtained using sonoelectrochemical deposition with others that synthesized using plain electrochemical deposition, the photocurrent density of the former electrode was ∼2.2 times higher than that of the latter when biased at 1.0 V (vs. Ag/AgCl). The reproducible photocurrent response under intermittent illumination demonstrated the excellent stability of the composite electrode. Such kind of composite electrode material will have many potential applications in solar cell and other fields.